Family support and motivational factors in weight loss among children and adolescents—a cross-sectional study - Wąsacz, Małgorzata; Ochojska, Danuta; Sarzyńska, Izabela; Bartkowska, Oliwia; Stańczyk, Szymon; Błajda, Joanna; Frej, Damian; Kopańska, Marta (Frontiers in Nutrition, 2025)
IntroductionChildhood and adolescent obesity is an increasing public health concern. The effectiveness of overweight treatment in this population depends on multiple factors, including the level of motivation, emotions associated with behavioral change, and family support.AimThe aim of this study was to analyze the levels of motivation, emotions, and self-esteem among overweight and obese children and adolescents, and to identify the potential role of family support in the process of changing dietary habits.Materials and methodsThe study involved 100 participants aged 10 to 18, recruited from three settings: school, hospital, and rehabilitation health resort environments (sanatoria). Inclusion criteria comprised overweight or obesity (BMI ≥ 85th percentile), regular school attendance, and parental consent. Exclusion criteria included chronic illness, metabolic or genetic disorders, and pharmacotherapy affecting body weight. A custom-designed questionnaire was used, along with elements of individual interviews. We hypothesized that higher levels of family support would be associated with greater motivation and longer maintenance of healthy lifestyle changes. The analysis focused on the duration of maintaining healthy habits, eating control, self-esteem, and emotions accompanying weight loss. Statistical analysis included significance tests and group comparisons.ResultsMost participants reported short-term attempts to change habits (1–5 days), and only 16% maintained a diet for 28 days. A significant portion experienced negative emotions such as anxiety, shame, or guilt, particularly among high school students. Additionally, 67% of respondents stated that their body weight influenced their self-perception. A statistically significant relationship was found between BMI category and dissatisfaction with one’s weight (p = 0.0261). The interviews revealed the critical role of parental attitudes in sustaining the child’s motivation.ConclusionThe findings highlight the need to include emotional and family-related components in overweight and obesity treatment programs for children. A comprehensive, individualized approach increases the likelihood of lasting lifestyle changes and improved psychological well-being in young patients.